Gas exchange and leaf contents in bell pepper under energized water and biofertilizer doses - Francisca R. M. Borges; Thales V. de A. Viana; Albanise B. Marinho; Luis G. Pinheiro Neto; Benito M. de Azevedo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the effect of energized water and bovine biofertilizer doses on the gas exchange and NPK contents in leaves of yellow bell pepper plants. The experiment was conducted at the experimental area of the Federal University of Ceará, in Fortaleza-CE, Brazil, from June to November 2011. The experiment was set in a randomized block design, in a split-plot scheme; the plots were composed of treatments with energized and non-energized water and the subplots of five doses of liquid biofertilizer (0, 250, 500, 750 and 1000 mL plant-1 week-1). The following variables were analyzed: transpiration, stomatal conductance, photosynthesis and leaf contents of nitrogen (N), phosphorus (P) and potassium (K). Water energization did not allow significant increases in the analyzed variables. The use of biofertilizer as the only source of fertilization was sufficient to provide the nutrients N, P and K at appropriate levels for the bell pepper crop.